2017
DOI: 10.1002/2017gl074743
|View full text |Cite
|
Sign up to set email alerts
|

Aspect dependence of Langmuir parametric instability excitation observed by EISCAT

Abstract: Recent studies of X‐mode wave heating experiments observed by EISCAT (European Incoherent Scatter Scientific Association UHF radar indicate that parametric instability (PI) can be excited unexpectedly. In this paper, we reinvestigate the ionospheric heating experiment on 21 and 22 October 2012 in details. The observed HF‐enhanced ion lines (HFILs) and HF‐enhanced plasma lines (HFPLs) observed during the experiments present dependence on the heating incidence angles. The observational evidence and numerical cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This study shows the high rate GNSS data along with incoherent scatter radar can be used to study small scale density perturbation induced by HF heating. One of the recently debated topics in the ionospheric active experiment research is aspect angle‐dependent density enhancement during X mode heating at EISCAT (Blagoveshchenskaya et al., 2011a, 2011b; M. Rietveld & Senior, 2020; Senior et al., 2013; Wang & Zhou, 2017). In fact, an apparent density increase was observed through X‐mode heating in EISCAT Ne before the GLONASS passing (see 12:26 UT in Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…This study shows the high rate GNSS data along with incoherent scatter radar can be used to study small scale density perturbation induced by HF heating. One of the recently debated topics in the ionospheric active experiment research is aspect angle‐dependent density enhancement during X mode heating at EISCAT (Blagoveshchenskaya et al., 2011a, 2011b; M. Rietveld & Senior, 2020; Senior et al., 2013; Wang & Zhou, 2017). In fact, an apparent density increase was observed through X‐mode heating in EISCAT Ne before the GLONASS passing (see 12:26 UT in Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, Wang et al (Wang X et al, 2016a(Wang X et al, , b, 2018Wang X and Zhou C, 2017) and Feng T et al (2020) claimed that some effects similar to those excited by the O mode pumping were excited by the X mode pumping at the European Incoherent Scatter Scientific Association (EISCAT) facility. Wang X et al (2016a) proposed that a small parallel component of the X mode pumping might satisfy the threshold of parametric decay instability (PDI) in an inhomogeneous plasma, and that a modified kinetic electron distribution might satisfy the PDI frequency matching condition.…”
Section: Introductionmentioning
confidence: 99%
“…This is because (1) X‐mode pump waves do not have a strong enough parallel electric field at the X‐mode reflection height and (2) the frequency matching condition is not satisfied at the X‐mode reflection height. It is surprising that HFPLs and HFILs resulting from X‐mode pumping have been directly observed in recent X‐mode heating experiments (Blagoveshchenskaya et al, 2014, 2015, 2017; Wang X et al, 2016a, b; Wang X and Zhou C, 2017). Optical emissions (Blagoveshchenskaya et al, 2014), artificial small‐scale FAIs (Blagoveshchenskaya et al, 2011, 2013), narrow SEEs (Blagoveshchenskaya et al, 2015, 2017), HFILs, and HFPLs (Blagoveshchenskaya et al, 2014, 2015, 2017; Wang X et al, 2016b; Wang X and Zhou C, 2017) have been observed during these recent X‐mode heating experiments.…”
Section: Introductionmentioning
confidence: 99%
“…It is surprising that HFPLs and HFILs resulting from X‐mode pumping have been directly observed in recent X‐mode heating experiments (Blagoveshchenskaya et al, 2014, 2015, 2017; Wang X et al, 2016a, b; Wang X and Zhou C, 2017). Optical emissions (Blagoveshchenskaya et al, 2014), artificial small‐scale FAIs (Blagoveshchenskaya et al, 2011, 2013), narrow SEEs (Blagoveshchenskaya et al, 2015, 2017), HFILs, and HFPLs (Blagoveshchenskaya et al, 2014, 2015, 2017; Wang X et al, 2016b; Wang X and Zhou C, 2017) have been observed during these recent X‐mode heating experiments. Vas'kov and Ryabova (1998) reported that the UH waves can also be excited by X‐mode heating through PDI near the reflection height.…”
Section: Introductionmentioning
confidence: 99%